ATRIBUTOS QUÍMICOS DO SOLO E PRODUTIVIDADE DA SOJA INFLUENCIADOS PELA CALAGEM SUPERFICIAL E ADUBAÇÃO NITROGENADA NO SISTEMA PLANTIO DIRETO - Haliski, Adriano (2015)
Nitrogen fertilization can increase the efficiency of surface liming on soil acidity correction and benefit crop production in long term no-till systems. Because the soil organic matter content under no-till is high, especially in the soil surface layers, the aluminum (Al) toxicity may be low, even in high acidity conditions. This study was carried out with the purpose of evaluate the soil chemical attributes, grain yield, and critical levels for the development of soybean after surface application of lime and ammoniacal nitrogen (N-NH4NO3) in crops of autumn-winter predecessors. The experiment was conducted in Ponta Grossa, Parana State, Brazil, on a loamy, kaolinitic, thermic Typic Hapludox (Oxisol) under long term continuous no-till (26 years). The experimental design used was a randomized block, in a split plot arrangement, with three replications. In the plots, were applied, in May 2004, four rates of lime on the soil surface (0, 4, 8, and 12 t ha-1) and, in the subplots, were applied annually, since 2004, four rates of N-NH4NO3 (0, 60, 120 and 180 kg ha-1) in top dressing in the black oat or wheat crops. In crop rotation was used corn, soybeans or beans in the spring-summer season and black oat or wheat in the autumn-winter season. Soybean was sown in November 2007 (cv. CD 214 RR), 2009 (cv. CD 206 RR), 2010 (cv. BMX Apolo RR), 2012 (cv. NA 5909 RG), and 2013 (cv. BMX Ativa RR). Soil samples were collected annually before soybean sowing at the 0–0.05, 0.05–0.10, and 0.10–0.20 m depths. Surface liming increased pH and the contents of exchangeable Ca2+ and Mg2+, and reduced the content of exchangeable Al3+ to a depth of 0.20 m. Nitrogen fertilization reduced pH and the contents of exchangeable Ca2+ and Mg2+, especially to a depth of 0.10 m, and increased the content of exchangeable Al3+ to a depth of 0.20 m. Surface application of lime increased the soybean grain yields for all N-NH4NO3 rates used in black oat or wheat crops. In unlimed plots, acidification caused by nitrogen fertilization severely limited the soybean grain yield. The critical levels of pH in CaCl2, base saturation, exchangeable Al3+, and Al3+ saturation in the 0–0.20 m layer for soybean production were 4.9, 33%, 8.0 mmolc dm-3, and 30%, respectively. Surface application of lime proved to be a key practice to ensure high soybean yields when high ammoniacal fertilizer rates are applied frequently in no-till systems.